The Effect of Investment in Information Technology on the Performance of Firms Listed at Palestinian Security Exchange - Naser Abdelkarim; Said Alawneh (My University, 2009)
This study aims at testing the effect of investment in information technology on the performance of firms listed at Palestinian Security Exchange according to accounting performance measures namely return on assets (ROA), return on equity (ROE), return on sales (ROS), sales growth, and the market value of the firm measured by Tobin's q. On the other hand, the research is an attempt to know which one of them is more influenced by the investment in information technology. The sample of the study consisted of (22) Companies listed on the Palestinian Stock Exchange during the period 1998-2003.The researcher used the multi regression in order to analyze and test the general hypothesis. The study revealed that the investment in information technology has a positive effect on accounting performance measures, and the market value of the firms. This effect appears after two years. Due to this the study recommends that the companies must invest in the information technology and communication because it has a positive effect on the market value and the financial performance. The Palestinian authority must work to liberate the technology and communication sectors in order to make it more competitive, by issuing a law to organize and this sector.

هدفت هذه الدراسة إلى اختبار أثر الاستثمار في تكنولوجيا المعلومات على الأداء المالي للشركة وذلك وفقاً لمقاييس الأداء المحاسبية التقليدية (العائد على الأصول ((ROA، العائد على حقوق الملكية ((ROE، والعائد على المبيعات (ROS)، و(نمو المبيعات) والقيمة السوقية للشركة التي تم احتسابها وفقاً لنموذج Tobin's q، ومعرفة أيهما أكثر تأثراً بالاستثمار في تكنولوجيا المعلومات. تمثل مجتمع الدراسة بالشركات المساهمة العامة المدرجة في سوق فلسطين للأوراق المالية، حيث تم اختيار عينة مكونة من اثنتي وعشرون شركة (22) بعد تحقيقها لشروط معينة خلال فترة الدراسة (1998-2003). تم استخدام نماذج الانحدار لتحليل البيانات واختبار الفرضيات على أساس التباطؤ الزمني. توصلت الدراسة إلى وجود أثر للاستثمار في تكنولوجيا المعلومات على مقاييس الأداء المحاسبية: العائد على الأصول (ROA)، العائد على حقوق الملكية (ROE)، العائد على المبيعات (ROS)، معدل نمو المبيعات وأن هذا الأثر يظهر خلال سنتين على الأقل من سنة الإنفاق. وأن هناك أثراً للاستثمار في تكنولوجيا المعلومات على القيمة السوقية للشركة حسب نموذج Tobin's q وأن هذا الأثر يظهر خلال سنتين من تاريخ القيام به. وبناء على ذلك توصي الدراسة بضرورة الاهتمام بالاستثمار في تكنولوجيا المعلومات في الشركات الفلسطينية لما له من اثر على اداء الشركة في المدى البعيد، كما انه من الضروري ان تقوم السلطة او الجهات الحكومية بتحرير قطاع الاتصالات والتكنولوجيا ليصبح اكثر تنافسيا ، فضلا عن ضرورة العمل على إصدار قانون لتنظيم هذا القطاع.
مدى تأثير الاستثمار في تكنولوجيا المعلومات على الأداء المالي للشركات المساهمة العامة المدرجة في سوق فلسطين